Role of vitamin D in the formation of abnormal uterine bleeding in the pubertate period - Dynnik , V.O.; Dynnik, O.O.; Druzhinina , A.E. (Medicni Perspektivi, 2022)
The problem of the participation of vitamin D in the pathogenesis of various diseases has been attracted the attention of scientists in recent years. Vitamin D deficiency is regarded as a global problem that increases the risk of many chronic diseases. More recently, the emphasis has shifted to the non-skeletal effects of vitamin D. A lot of literature suggests that vitamin D plays an important role in the regulation of processes in the ovaries that determine female fertility, female reproductive potential. Vitamin D receptor enzymes involved in its metabolism are expressed in both the central and peripheral reproductive organs (hypothalamic-pituitary system, ovaries, uterus, placenta). All of this suggests that vitamin D is involved in the regulation of menstrual function. The aim of the study is to identify the relationships between gonadotropic and steroid hormones with the content of vitamin D in menstrual disorders in adolescent girls by type of abnormal uterine bleeding (AUB). 167 adolescent girls with AUB were examined. The levels of Luteinizing hormone (LH), Follicle-stimulating hormone (FSH), Prolactin (PRL), total estradiol (E2), testosterone (T), cortisol (C), vitamin D were determined. It was revealed that in 92.1% of girls with AUB have a decrease in the level of vitamin D, and 53.9% of them have a sharp reduce of its. A factorial model of the relationship between pituitary-gonadal hormones and vitamin D, on the basis of which it may be assumed that vitamin D makes a significant contribution to the formation of AUB in adolescence. It participates in the mechanisms of stimulation of gonadotropins, affects the activity of sex hormones through the promoters of receptors located both in the hypothalamic-pituitary region and in the periphery in the ovaries. This is evidenced by factor weights, which serve as analogues of the correlation ratios and show the degree of interconnection between the variables in the factors selected. The changes in the content of vitamin D revealed indicate the need and expediency of its determination in the blood of patients with AUB during puberty for early diagnosis of its abnormalities and timely prevention of serious complications in the future.